Modeling and optimization of natural gas processing and production networks - Alsobhi, Saad (University of Waterloo, 2015)
Natural gas is a nonrenewable energy source, so it is important to use it and utilize it in a sustainable manner. Globally, about 25% of energy consumption is supplied and fulfilled by natural gas and this percentage will stay true for the foreseeable future. Today, the fluctuations in commodities prices and demands all necessitate the proper planning and coordination in natural gas industries. Moreover, the strict environmental regulations, continuous advancement in technologies and different customer requirements and specifications, all mandate seeking many pathway options and continuous evaluation of the technologies. Thus, the overall objective of this research is to provide a framework for the design, synthesis, analysis, and planning of a natural gas processing and production networks. The overall framework helps the decision maker in the natural gas industry to evaluate and select optimally the production pathways and utilization options by using the mathematical modeling and optimization techniques in order to maximize the value of natural gas resource. Toward this objective, a novel natural gas network has been synthesized for analysis and optimization. The developed network converts natural gas to LNG, condensate, LPG, gasoline, diesel, wax, and methanol as main products. The contributions of this dissertation fall mainly into three milestones; namely (1) simulation of natural gas network (2) mathematical formulation and optimization of the network and (3) sustainability assessment of the network. The first milestone addresses the rigorous steady state simulation of natural gas network. The simulation of key processing units helped in calculating accurately material and energy balances. Furthermore, the sensitivity analysis or what-if analysis was performed to determine the effect of different operating-parameters on products yield. The second milestone is the comprehensive mathematical formulation and optimization represented by both linear programming (LP) and mixed integer linear programming (MILP) models. Firstly, a deterministic operational LP model has been formulated and implemented on natural gas processing and production networks. Based on the yields obtained from the simulation, LP model was able to tackle different scenarios, such as, variations and fluctuations in natural gas flow rate, natural gas price, products price, and so on. Secondly, a comprehensive MILP model for the optimal design and operation of natural gas processing network was proposed. The MILP model addresses the different technologies and configurations available for the selection of key processing units. Also, it considers the different operating modes practiced in industry in terms of low, moderate, and severe restrictions to the specifications level. Thirdly, another MILP model for the optimal design and operation of natural gas production network has been developed. We were able to address the different routes for natural gas utilization. Finally, the third milestone is the sustainability assessment. The sustainability metrics or indicators were evaluated to investigate the sustainability dimensions and to address the economic, environmental, and societal aspects of the synthesized processing and production networks. The sustainability metrics proved to be useful in selecting pathways that are both economic and environmental friendly.
Keywords: Natural gas; modeling; optimization; processing network; production network; Chemical Engineering